“What Now?” vs. “Now It’s My Turn!” – Reflecting on Motherhood after the Children Have Left - Doebler, Marie-Kristin (Socialinė teorija, empirija, politika ir praktika, 2025)
Interested in being a mother and mothering across time, I compare two types of data: (a) interviews with middle-class mothers of grown-ups reflecting upon their prior (maternal) life in Germany, and (b) self-help books addressing parents in this life-phase, called the ‘empty nest’. My analysis reveals differing understandings and constructions of motherhood. The books homogenise being a mother and naturalise what a mother is, does and feels. Accordingly, women complete themselves and find self-fulfilment primarily as mothers, and thus, they struggle when children have moved out as this provides problems for mothering or even signifies the end of motherhood. Contrary to this, the interviews display much greater diversity: despite retrospectively construing images of comprehensive motherly care, gender differentiated life-courses and intensive mothering prior to children’s move out, the interviewees narratively present varying ways of being a mother and a dynamic balancing of motherhood with other sources of identity. Thus, their self-descriptions clash with the self-help depiction of static motherhood in books and uniform experiences of the nest emptiness. Rather than discussing a void and asking, “What now?”, the interviewees make sense of the lived temporality of motherhood and pragmatically deal with the changing needs for mothering. None of them suffers when they launch their children into independent life as they develop coping strategies in former life-course stages, continue to mother after the children have left home, and claim “Now it’s my turn!”
Keywords: Empty Nest; Gendered Parenthood; Life-Course; Motherhood; Social Constructionism